Sparkling wine international market structure and competitiveness - Karim Marini Thomé; Vitoria A. Leal Paiva (Wine Economics and Policy, 2020)
This paper aims to analyse the Sparkling Wine international market structure and competitiveness, focusing on the 2004-2018 period. It used the data regarding exports and imports of sparkling wine available in the International Trade Centre's Trade Map database. The method used to examine sparkling wine's international market structure and competitiveness consisted of calculation of: (i) Revealed Comparative Advantage (RCA); (ii) Relative Position in the Market (RPM); (iii) Hirschman-Herfindahl Index (HHI); and (iv) Net Export Index (NEI). The paper analyses the growth of the sparkling wine trade worldwide. It demonstrated that France had the greatest relative position in the market, followed by Italy and Spain. This same sequence was found in the revealed comparative advantage, highlighting the increased Italian export level. A high export market structure concentration was also shown. On the other hand, there was an unconcentrated import market structure, and, according to the NEI, it was possible to identify three groups composed of actors who were stable in terms of: i) exports based on domestic production (France, Italy and Spain); ii) trade, reflecting re-export (Singapore and the Netherlands); iii) imports, with strong domestic consumption (Germany, the United Kingdom, the United States of America, Australia, and Belgium).
Keywords: 330; Wine Competitiveness; market structure; sparkling wine; HHI; revealed comparative advantage